Native legumes from the Atlantic Rainforest and their potential for biomonitoring urban air pollution - Andrade, Guilherme Carvalho (2015)
In Southeastern Brazil, the city of Ipatinga is inserted in the Steel Valley Metropolitan Region, which is characterized by the predominance of steel industry, and also by the presence of one of the largest vehicle fleets in the country. Developing standardized biomonitoring methods with native plant species may be an economically viable option for assessing air quality across extensive urban areas, which usually cannot be achieved by instrumental monitoring due to cost issues. In this sense, the potential for biomonitoring airborne particles was evaluated in Caesalpinia echinata and C. ferrea aiming to test whether metal accumulation by the plants is related to leaf surface features. Plants were exposed in four urban sites for 90 days. A reference station was installed at Rio Doce State Park, 30 km away from the municipality. After the experimental period, plants were evaluated for trace-metal accumulation. Leaf surface roughness was evaluated in two hierarchical levels, through profilometry and atomic force microsocopy. Epicuticular waxes were characterized chemically through GC-MS and FTIR, and micromorphologically through scanning electron microscopy. Leaf tissue thickness was assessed through optical microscopy. Particle accumulation was higher in C. echinata, and was related to a lower roughness given by the epidermal tissue (macro- roughness), lower roughness given by the epicuticular wax deposition pattern (micro- roughness), the micromorphology of waxes in the form of a layer, and the wax chemical composition. The waxes of this species have lower amounts of hydrocarbons and ethers, conferring them a polar nature. These characteristics presumably render the leaf higher wettability, which is usually associated with decreased self-cleaning effect and a consequent increased particle accumulation. In contrast, C. ferrea showed reduced accumulation of particulate matter (PM), but a more well-defined response gradient across the exposure sites. Sites were a discriminant factor for cell height on the epidermal tissue, especially on the leaf adaxial surface, such tissue showing reduced thickness in plants exposed at the urban stations. The results suggest the use of C. echinata as a bioaccumulator of PM and C. ferrea as biosensor of urban pollution.